2012
DOI: 10.1007/s10787-012-0163-3
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of Curcuma longa extract in the treatment of painful knee osteoarthritis: a randomized placebo-controlled trial

Abstract: Curcuma longa Linn. is widely used for the treatment of disorders associated with inflammation and was evaluated for its safety and efficacy in the treatment of painful knee osteoarthritis (OA). This was a randomized, single blind, placebo-controlled trial. Total of 120 patients (37 males and 83 females) with primary knee OA received either placebo (400 mg twice daily) or NR-INF-02 (500 mg twice daily) or glucosamine sulphate (GS) (750 mg twice daily) alone or combination of NR-INF-02 and GS for 42 days. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
130
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(140 citation statements)
references
References 18 publications
2
130
0
8
Order By: Relevance
“…37 We also excluded one study because there was no relevant outcome 38 and one (abstract) because it was a duplicate of another excluded study. 39 Finally, we included seven studies [40][41][42][43][44][45][46] with a total of 797 participants. Key details of the included studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…37 We also excluded one study because there was no relevant outcome 38 and one (abstract) because it was a duplicate of another excluded study. 39 Finally, we included seven studies [40][41][42][43][44][45][46] with a total of 797 participants. Key details of the included studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…In four studies the proportion of participants with bilateral knee OA ranged from 37% 44 to 100%. 45 Three studies 42,43,46 did not report the proportion of participants with bilateral knee OA. The mean age of the participants ranged from 57 to 69 years, and the duration of intervention was between 4 and 16 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations